Analiza krótko- i długookresowych związków pomiędzy giełdami azjatyckimi a rynkiem europejskim i amerykańskim - Pielucha, Daria (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The aim of the article is to assess the relations between the Chinese and Japanese stock exchanges in relation to the American and European markets represented by the German market and to assess the impact of price fluctuations of the S&P500 and DAX indices on Asian stock exchange indices. In the study, the ADF test was used, according to which the degree of integration of the studied processes was determined and an appropriate class of distributed lag models and error correction was selected for the assessment of short- and long-term dependencies. The results of the conducted analysis clearly indicate that Asian exchanges are linked to both the American and German markets, but only in the case of index pairs NI225-DAX and SSEC-SP500 was the co-integration of processes confirmed, i.e. their joint pursuit of a long-term balance. In the case of the remaining pairs, co-integration has not been confirmed, which means that there is a spurious correlation and therefore, a correct analysis of the mutual relations in these cases allows only short-term relationships to be detected. The results of the article may be helpful in choosing an investment strategy on Asian exchanges adapted to its time horizon.
Keywords: Asian markets; distributed lag models; co-integration